AN OVERVIEW OF PERFORMANCE MEASUREMENT USING A BALANCED SCORECARD METHOD AT FAISAL ISLAMIC HOSPITAL OF MAKASSAR - Arfiah, Wihda; Rusmin, Muhammad; Syarfaini, Syarfaini; Nildawati, Nildawati; Alam, Syamsul (Homes Journal: Hospital Management Studies Journal, 2021)
Background:The Balanced Scorecard can translate organizational and strategic vision and mission into the operational goals and measure the performance for four different perspectives Objective:The study was aimed at finding out the overview of performance measurement using the Balanced Scorecard method at Faisal Islamic Hospital of Makassar. Method: The study was descriptive quantitative research involving 11869 patients/families of patients as research population and 403 employees as the samples gathered using a Stratified Random Sampling technique. The collected data were then analyzed univariately. Result:The results of the study revealed that on the costumers’ perspective, the customers’ acquisition was the only indicator showing the unfavorable result decreased by 4.64%. In the financial perspective, the ROI indicator and effectiveness ratio had decreased by 18.96% and 59.6%, both indicators were stated to be less good. In the Internal Business perspective in terms of service quality the BOR and ALOS ratio were said to be less good. From the perspective of Learning and Growth it was very good where all indicators were in accordance with the standards. The four perspectives of the Balanced Scorecard were very influential on the hospital’s performance. Conclusion:By improving the costumers’ acquisition, the hospital income would increase as well.